Investigación del mecanismo de la actividad antifúngica del citral contra Cladosporium sphaerospermum Penz. - Pinheiro de Menezes, Camilla; Alves de Lima Perez, Ana Luiza; Pereira de Sousa, Janiere; Abrantes Pereira, Julio; de Souza Pinheiro, Lílian; Araújo de Medeiros, Maria Alice; de Souza Alves, Millena; Alves de Oliveira Filho, Abrahão; de Oliveira Lima, Edeltrudes (Anales de Biología, 2022)
The aim of this study was to investigate the antifungal activity of citral against Cladosporium sphaerospermum, by determining the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC), effects on mycelial growth and conidia germination, and also investigated the possible action of citral in cell walls and cell membranes. The MIC of citral ranged from 128 to 256 µg / ml and the MFC ranged from 256 to 1024 µg/mL. The MIC50 and MFC50 were, respectively, 128 µg/mL and 256 µg/mL. Citral inhibited mycelial development and conidia germination and showed interaction with ergosterol. These data indicate that citral has strong antifungal activity, which may be related to its interaction with ergosterol.